Geometric Distribution and Earthquake Rupture Characteristics of the Northern Anqiu–Juxian Fault in the Tan–Lu Fault Zone, Eastern China - Ji, Haomin; Li, An; Zhang, Shimin; Zhang, Ji; Liu, Qing (Frontiers in Earth Science, 2022)
The Northern Anqiu–Juxian Fault (NAJF) is one of the most active faults in the Tan-Lu Fault Zone (TLFZ), which produced the Anqiu M 7 earthquake in 70 BC. However, there is no clear understanding of the surface rupture caused by this historical earthquake. In this study, we determined the earthquake rupture characteristics of the NAJF based on high-precision surveying, geophysical exploration and drilling profiles. Based on an analysis of 87 horizontal offsets of gullies, we estimated a characteristic offset of ∼ 5 m along the NAJF for a rupture length about 130 km. Geophysical exploration results revealed a shallow geometric distribution of stepovers in the NAJF. We concluded that the ∼ 5 m offset and the rupture length of about 130 km are both in agreement with an empirical relationship among the magnitude, offset, and rupture length and imply that the ∼ 1 km wide stepover could not have terminated ruptures in the Anqiu M 7 earthquake. The relationship among the coseismic offset, magnitude, and surface rupture length of a strike-slip fault show that the 70 BC Anqiu earthquake was more likely to have had a magnitude of M ∼ 7.5.